장시간 지속된 기능적 실성증에 대한 음성치료 1예 - 김보람; 우주현; Kim, Bo Ram; Woo, Joo Hyun (대한후두음성언어의학회지, 2022)
Functional aphonia is a disease in which normal vocal ability is suddenly lost. When voice therapy is started at an early stage, the prognosis is good. However, if the functional aphonia persists for a long time, there is a possibility that the voice disorder may become fixed, though reports of these characteristics are rare. The authors experienced a patient with functional aphonia that occurred in adolescence and lasted for 7 months and reported the result of treatment.